Online Prostitution in Hindu Law Perspective - I Nyoman Alit Putrawan (International Proceeding On Religion, Culture, Law, Education, And Hindu Studies, 2022)
Today's prostitution can be easily found, because only by using social media applications, prostitutes can carry out sex transactions. Prostitution is a classic problem that is very difficult to eradicate from time to time, because some are covert and many parties use it for various reasons. Among other things, family problems, economy, lifestyle and so on. The impact is certainly disturbing the community. Whereas in national law and Hindu law the sanctions are very clear, but this practice still occurs.Legal theory is used to disscuss it. The results of data analysis in this research paper are presented in descriptive analytical or informal form. With data collection methods using primary data and secondary data sources, by tracing existing documents, the technique of determining informants is the Snowballing Sampling model technique. The existence of prostitution has been existed long before social media developed, prostitution occurred in ancient times (Greece). The legal consequences of prostitution according to Hindu law can be fined up to the death penalty according to Manawa Dharmasastra, in customary law sanctions are Sangaskara danda (priyascitta) in national law, perpetrators can be snared by the Criminal Code and UUITE. The role of law enforcement in handling prostitution must be maximized by collaborating with religious leaders, traditional leaders and the community to provide vocations and counseling to the community against the dangers and threats of punishment for prostitutes on social media.